Frontalis Sling Procedure for Blepharoptosis Following Trauma to the Head - Smilja, Tudjarova Gjorgova; Blagoja, Srbov; Karadjinova, Nina (RA Journal of Applied Research, 2022)
Blepharoptosis is a relatively common condition and the treatment remains unpredictable as the choice of one of the many surgical options relies on the cause of the ptosis. We report a case of severe blepharoptosis, the surgical technique, the materials that were used for the post-op outcomes. Frontalis suspension is a commonly used surgery that is indicated in patients with blepharoptosis and poor levator muscle function. This surgery connects the eyelid to the brow with a sling material and utilizes the power of the frontalis muscle to elevate the poorly functioning eyelid. In our, discussion we propose possible treatments in severe blepharoptosis such as resection and advancement of the levator aponeurosis, The Whitnall sling procedure, the frontalis muscle flap procedure, use of fascia lata, and Müller's muscle-conjunctival resection surgery. We elaborate on our predilection for use of the Frontalis sling procedure. Even though our patients may suggest that using general anesthesia is better for their comfort we prefer, and recommend the use of local anesthesia with intravenous sedation due to the advantage of the ease in balancing the lids during surgery. Deciding on which technique to use depends on many factors such as the operator experience, their comfort level with various techniques, the degree of ptosis of levator muscle function.